The relationship between the leadership of the head of room and work environment with performance of nurse in Pringsewu Region General Hospital - Marthalena, Yenny; Aisyah, Siti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Nurses' performance is still insufficient in providing services to patients and they are often late when coming to work. The head of the room also said that relations between colleagues were still not good enough in the work environment and that internet access in the hospital still not good and lighting in the inpatient room was still lacking. Likewise, the nurse said that the head of the room was still lacking in communicating with the nurses. This research aims to determine the relationship between the leadership style of the head of the room and the work environment with the performance of nurses at the Pringsewu Region General Hospital. The performance of inpatient room nurses is still not good in providing services to patients and they are often late when coming to work, so the formulation of the problem in this research is what is the relationship between the leadership style of the head of the room and the work environment with the performance of nurses at the Pringsewu Region General Hospital? This research uses a quantitative type of research. The population was 129 respondents with a sample of 99 respondents. The sampling technique is purposive sampling. Univariate and bivariate data analysis. The results of research based on univariate analysis show that the leadership style of the majority of room heads is good leadership style, 74 (74.7%). The majority of work environments are in the good category, 49 (49.5%). The majority of implementing nurses performed well at 79 (78.8%). Bivariate analysis using the gamma test obtained a p-value of 0.000 (<0.05). The results of the research show that there is a relationship between the leadership style of the head of the room and the work environment and the performance of nurses at the Pringsewu Regional General Hospital. The suggestion in this research is to increase knowledge in the field of nursing in order to provide professional nursing performance and improve the quality of nursing services.